Constitutive, but not challenge-induced, interleukin-10 production is robust in acute pre-pubescent protein and energy deficits: new support for the tolerance hypothesis of malnutrition-associated immune depression based on cytokine production in vivo. - Monk, J; Steevels, T; Hillyer, L; Woodward, B (2011)
The tolerance model of acute (i.e., wasting) pre-pubescent protein and energy deficits proposes that the immune depression characteristic of these pathologies reflects an intact anti-inflammatory form of immune competence that reduces the risk of autoimmune reactions to catabolically released self antigens. A cornerstone of this proposition is the finding that constitutive (first-tier) interleukin(IL)-10 production is sustained even into the advanced stages of acute malnutrition. The IL-10 response to inflammatory challenge constitutes a second tier of anti-inflammatory regulation and was the focus of this investigation. Weanling mice consumed a complete diet ad libitum, a low-protein diet ad libitum (mimicking incipient kwashiorkor), or the complete diet in restricted daily quantities (mimicking marasmus), and their second-tier IL-10 production was determined both in vitro and in vivo using lipopolysaccharide (LPS) and anti-CD3 as stimulants of innate and adaptive defences, respectively. Both early (3 days) and advanced (14 days) stages of wasting pathology were examined and three main outcomes emerged. First, classic in vitro systems are unreliable for discerning cytokine production in vivo. Secondly, in diverse forms of acute malnutrition declining challenge-induced IL-10 production may provide an early sign that anti-inflammatory control over immune competence is failing. Thirdly, and most fundamentally, the investigation provides new support for the tolerance model of malnutrition-associated inflammatory immune depression.